Navigating HIV citizenship: identities, risks and biological citizenship in the treatment as prevention era. (17th February 2019) - Young, Ingrid; Davis, Mark; Flowers, Paul; McDaid, Lisa M.
Abstract : The use of HIV Treatment as Prevention (TasP) has radically changed our understandings of HIV risk and revolutionised global HIV prevention policy to focus on the use of pharmaceuticals. Yet, there has been little engagement with the very people expected to comply with a daily pharmaceutical regime. We employ the concept of HIV citizenship to explore responses by people living with HIV in the UK to TasP. We consider how a treatment-based public health strategy has the potential to reshape identities, self-governance and forms of citizenship, domains which play a critical role not only in compliance with new TasP policies, but in how HIV prevention, serodiscordant relationships and (sexual) health are negotiated and enacted. Our findings disrupt the biomedical narrative which claims an end to HIV through scaling up access to treatment. Responses to TasP were framed through shifting negotiations of identity, linked to biomarkers, cure and managing treatment. Toxicity of drugs – and bodies – were seen as something to manage and linked to the shifting possibilities in serodiscordant environments. Finally, a sense of being healthy and responsible, including appropriate use of resources, meant conflicting relationships with if and when to start treatment. Our research highlights how HIV citizenship in the TasP era is negotiated and influenced by intersectional experiences of community, health systems, illness and treatment. Our findings show that the complexities of HIV citizenship and ongoing inequalities, and their biopolitical implications, will intimately shape the implementation and sustainability of TasP.